RNase Therapy Assessed by Magnetic Resonance Imaging Reduces Cerebral Edema and Infarction Size in Acute Stroke - Walberer, Maureen; Tschernatsch, Marlene; Fischer, Silvia; Ritschel, Nouha; Volk, Kai; Friedrich, Carolin; Bachmann, Georg; Mueller, Clemens; Kaps, Manfred; Nedelmann, Max; Blaes, Franz; Preissner, Klaus T.; et al. (Current Neurovascular Research, 2009)
Ischemic stroke causes cell necrosis with the exposure of extracellular ribonucleic acid (RNA) and other intracellular material. As shown recently, extracellular RNA impaired the blood-brain-barrier and contributed to vasogenic edema-formation. Application of ribonuclease 1 (RNase 1) diminished edema-formation and also reduced lesion volume in experimental stroke. Here we investigate whether reduction of lesion volume is due to the reduction of edema or of other neuroprotective means. Neuroprotective and edema protective effects of RNase 1 pretreatment were assessed using a temporary middle cerebral artery occlusion (MCAO) model in rats. Lesion volume was assessed on magnetic resonance imaging (MRI). T2- relaxation-time and midline-shift as well as brain water content (wet-dry-method) were measured to quantify edema formation. The impact of edema formation on infarct volume was evaluated in craniectomized animals. Exogenous RNase 1 was well tolerated and reduced edema-formation and infarct size (26.7% ± 10.7% vs. 41.0% ± 10.3%; p<0.01) at an optimal dose of 42 μg/kg as compared to placebo. Craniectomized animals displayed a comparable edema reduction but no reduction in infarct size. The present study introduces a hitherto unrecognized mechanism of ischemic brain damage and a novel neuroprotective approach towards acute stroke treatment.
Keywords: edema